Perception of Agrobacterium tumefaciens flagellin by FLS2XL confers resistance to crown gall disease - Fuerst, Ursula; Zeng, Yi; Albert, Markus; Witte, Anna Kristina; Fliegmann, Judith; Felix, Georg (Nature Plants, 2020)
Bacterial flagella are perceived by the innate immune systems of plants1 and animals2 alike, triggering resistance. Common to higher plants is the immunoreceptor FLAGELLIN-SENSING 2 (FLS2)3, which detects flagellin via its most conserved epitope, flg22. Agrobacterium tumefaciens, which causes crown gall disease in many crop plants, has a highly diverged flg22 epitope and evades immunodetection by plants so far studied. We asked whether, as a next step in this game of ‘hide and seek’, there are plant species that have evolved immunoreceptors with specificity for the camouflaged flg22Atum of A. tumefaciens. In the wild grape species Vitis riparia, we discovered FLS2XL, a previously unknown form of FLS2, that provides exquisite sensitivity to typical flg22 and to flg22Atum. As exemplified by ectopic expression in tobacco, FLS2XL can limit crown gall disease caused by A. tumefaciens.
CRIS-Team Scopus Importer:2020-03-09